The effects economic usage of standardization of buffalo milk compared with non - standardized for production of fresh Mozzarella cheese (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Cheese is one of the first and most popular manufactured food products. What perhaps started out as an accidental curdling of milk has been further defined into cheese making. Over several thousand years, cheese making has advanced from an art to near science. Cheese varieties have proliferated to suit varied conditions and requirements, especially during the last decade or so.Actually, new cheeses are often formulated when mistakes happen, so there well may be truth in the tale. This study is done to research the examinations for production of mozzarella cheese, after research and analyses of physical-chemical peculiar feature of milk. We have followed the processes from drying of cheese until preparing it for market, physical-chemical peculiar feature. We carried out three experiments for each milk-kind. For every experiment, we took three patterns and analyzed. Â Production of this sort of cheese, the application of producing technology and the supply of Kosovaâ€™s trade market with mozzarella cheese is the objective of this presentation work research.